Interpersonal climate and moral conduct in competitive sport: A dual-route model with serial mediation - Ziqi Wang; Taoming Liu; Siyu Hong; Wenjun Wang; Fenglin Wang (PLoS ONE, 2025)
Background To investigate how coaching leadership styles influence athletes’ moral conduct, this study explored the direct and indirect effects of democratic and autocratic leadership behaviors on prosocial and antisocial behaviors in sport. Method A cross-sectional survey was conducted among 1,239 competitive athletes from multiple sports, measuring leadership perception, goal orientation, and moral disengagement. Key results Democratic leadership significantly predicted higher prosocial behavior and lower antisocial tendencies, while autocratic leadership showed the opposite pattern. Implications These effects were mediated by athletes’ task and ego orientation, as well as their level of moral disengagement. The findings highlight the broader relevance of ethical, knowledge-based leadership in cultivating sustainable behavioral outcomes in sports. These results support social cognitive and moral disengagement theory by revealing how internal cognitive-motivational factors transmit leadership influence. The study contributes to both sport psychology and leadership literature by identifying key mediating mechanisms and clarifying the behavioral implications of different leadership approaches. Practically, within the context of Chinese elite sport, the findings suggest that fostering more democratic leadership styles may be associated with more ethical conduct and support athletes’ longer-term development, although cross-cultural and longitudinal research is needed before drawing broader causal conclusions.